Delavski predstavniki v organih vodenja in nadzora družb z omejeno odgovornostjo - Franca, Valentina (Delavci in delodajalci, 2019)
The Slovenian employee participation legislation does not make any distinction between the legal organizational forms of corporate entities as regards election or appointment of the works council and the board-level employee representatives. However, workers in limited liability companies may, because of insufficient legal provisions, experience much more challenging obstacles than workers employed in public limited companies. In the article below, the authors analyse and present possible legal solutions for enabling equal position of employees in the implementation of employee participation in limited liability companies.
Keywords: board-level employee representatives; delavci; družbe z omejeno odgovornostjo; employee participation; limited liability company; nadzorni organi; soupravljanje; works council